Quick & easy sewing stylish, speedy designs for your home - Hardy, Emma
Quick & Easy Sewing features 35 simple step-by-step projects that use nothing more than the most basic of sewing skills. Discover cozy and colorful scatter pillows, stylish drapes and shades, elegant table linens, handy storage bags and baskets, a comfy pillow for a garden bench, and even a cool play tent for the kids to run riot in--these are just a few of the ideas that Emma Hardy has designed using readily available fabrics and trims. Quick & Easy Sewing is also illustrated throughout using specially-commissioned photographs and easy-to-follow step-by-step diagrams, making it the perfect book for people who are big on ideas but short of time. Whether your home is a traditional country cottage or a modern warehouse-style apartment, you're sure to find plenty of ideas to inspire you.